Resin composition

JP2025031441AActive Publication Date: 2025-03-07NANYA PLASTICS CORP
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2023191196
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-23
Filing Date
2023-11-08
Publication Date
2025-03-07
Estimated Expiration
2043-11-08

AI Technical Summary

Benefits of technology

【0013】 上記に基づき、本発明の樹脂組成物は、銅箔基板に適用される場合、高ガラス転移温度(250℃以上)と低誘電正接(0.002以下)とを達成可能である。加えて、本発明の樹脂組成物は非極性骨格構造を有するため電界中で分極しにくく、これにより誘電率を大幅に低下させる(3.2以下)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031441000001
    Figure 2025031441000001
  • Figure 2025031441000002
    Figure 2025031441000002
  • Figure 2025031441000003
    Figure 2025031441000003
Patent Text Reader

Abstract

To provide materials for high-frequency printed circuit boards that have both high glass transition temperature and low dielectric loss tangent, as well as excellent electrical properties.SOLUTION: The disclosure provides a resin composition which includes: 30 wt.% to 60 wt.% of a bismaleimide resin; 1 wt.% to 10 wt.% of a liquid rubber resin; and 20 wt.% to 50 wt.% of a filler, based on the total weight of the resin composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition, and in particular to a resin composition. [Background technology]

[0002] In recent years, with the development of 5G and millimeter wave communications, higher frequencies (6 to 77 GHz) have been applied to mobile phones, base stations, servers, etc., and it is necessary to use board materials for higher frequencies to be suitable for 5G high frequencies. In addition, copper-clad boards also need to be developed to reduce the dielectric properties. In the current low-dielectric formulation, a certain ratio of liquid rubber can be added to reduce the dielectric tangent to less than 0.0020, but the glass transition temperature is low. For this reason, one of the urgent issues in the field of printed circuit boards is how to develop materials that have the properties of high-frequency printed circuit boards, such as materials with both high glass transition temperatures and low dielectric tangents, as well as excellent electrical properties. Summary of the Invention [Problem to be solved by the invention]

[0003] The present invention provides a resin composition, comprising, based on the total weight of the resin composition, 30% by weight to 60% by weight of a bismaleimide resin, 1% by weight to 10% by weight of a liquid rubber resin, and 20% by weight to 50% by weight of a filler. [Means for solving the problem]

[0004] In one embodiment of the invention, the bismaleimide resin comprises DCPD-BMI, KI-50P, KI-70, or a combination thereof.

[0005] In one embodiment of the invention, the liquid rubber resin comprises LDM-03-07, LDM-02, 1,2-SBS, or a combination thereof.

[0006] In one embodiment of the present invention, the resin composition further contains 0.1% by weight to 3% by weight of a coupling agent, and 0.1% by weight to 2% by weight of a catalyst.

[0007] In one embodiment of the present invention, the resin composition further contains 10% by weight to 20% by weight of a flame retardant.

[0008] The present invention provides an electronic component including a substrate formed from the resin composition.

[0009] In one embodiment of the present invention, the glass transition temperature of the substrate is 250° C. or higher.

[0010] In one embodiment of the invention, the substrate has a dielectric loss tangent of less than or equal to 0.002 at a frequency of about 10 GHz.

[0011] In one embodiment of the invention, the substrate has a dielectric constant of less than or equal to 3.2 at a frequency of about 10 GHz.

[0012] In one embodiment of the invention, the substrate is a copper foil substrate. Effect of the Invention

[0013] Based on the above, when the resin composition of the present invention is applied to a copper foil substrate, it can achieve a high glass transition temperature (250°C or higher) and a low dielectric tangent (0.002 or lower). In addition, since the resin composition of the present invention has a non-polar skeleton structure, it is difficult to polarize in an electric field, which significantly reduces the dielectric constant (3.2 or lower). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The following describes in detail the embodiments of the present invention. The implementation details provided in the embodiments are for illustrative purposes, and are not intended to limit the protection scope of the present invention. Those skilled in the art can modify or change these implementation details according to the actual implementation requirements.

[0015] Ranges may be expressed herein as from "about" one particular value to "about" another particular value, which may be expressed directly as the one particular value and / or the other particular value. When a range is expressed, in another embodiment, it includes the one particular value and / or to the other particular value. Similarly, when values ​​are expressed as approximations, by use of the antecedent "about," it is to be understood that the particular value forms another embodiment. It is to be further understood that the endpoints of each range may or may not be expressly related to the other endpoint.

[0016] In this embodiment, non-limiting terms (eg, may, capable, or similar terms) refer to non-essential or optional implementations, inclusions, additions, or presences.

[0017] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. Furthermore, it should be understood that terms (e.g., terms defined in commonly used dictionaries) should be interpreted to have a meaning consistent with the meaning in the relevant technical context, and should not be interpreted in an idealized or overly formal sense unless expressly defined.

[0018] As used herein, a so-called "divalent organic group" is an organic group that has two bonding positions, and the "divalent organic group" is capable of forming two chemical bonds via these two bonding positions.

[0019] The present invention provides a resin composition, which contains, based on the total weight of the resin composition, 30% to 60% by weight of a bismaleimide (BMI) resin, 1% to 10% by weight of a liquid rubber resin, and 20% to 50% by weight of a filler. The present invention combines the bismaleimide resin with the liquid rubber resin and the filler, and can improve the heat resistance of the high frequency board material and reduce the dielectric tangent of the high frequency board material.

[0020] In some embodiments, based on the total weight of the resin composition, the weight percentage of the bismaleimide resin is 30% to 60% by weight, such as 35%, 45%, or 55% by weight.

[0021] In some embodiments, the bismaleimide resin has a structure represented by formula (1): [ka] Here, L represents a dicyclopentadienyl group, a divalent organic group derived from a phenol compound, or a combination thereof; L 1 and L 2 represents a divalent organic group derived from a phenol compound, and m represents an integer of 0 to 18.

[0022] In some embodiments, the phenolic compound includes phenol. In some embodiments, the divalent organic group is preferably a divalent organic group including a maleimide group. In some embodiments, L is preferably a combination of dicyclopentadienyl and a divalent organic group derived from a phenolic compound. In some embodiments, L represents the following formula (1-1), the following formula (1-2), the following formula (1-3), or a combination thereof: * represents the attachment position. In some embodiments, L 1 and L 2 respectively represent the following formula (1-4), * represents the bond position. [ka]

[0023] In some embodiments, the bismaleimide resin has a structure represented by formula (2): [ka] Here, m represents an integer of 0 to 18, and preferably 2 to 10.

[0024] For example, the synthesis method of bismaleimide resin includes the following: First, 1 mole of dicyclopentadiene phenol resin (manufactured by Songyuan Co., Ltd., trade name ERM6140, weight average molecular weight 1,300) and 1.25 moles of 4-halonitrobenzene (wherein halogen can be fluorine, chlorine, bromine, or iodine) are added to 6 moles of dimethylacetamide (DMAC) used as a reaction solution, and reacted at a temperature of 120°C for 300 minutes to carry out a nitration reaction. Then, hydrogen gas is introduced to form a modified dicyclopentadiene-type diamine, and reacted at a temperature of 90°C for 480 minutes to carry out a hydrogenation reaction. Next, to produce a second resin, which is a bismaleimide resin whose main chain contains a dicyclopentadiene structure (abbreviated as DCPD-BMI) and has a structure represented by formula (2) and whose average molecular weight may be 800 to 10,000, preferably 1,000 to 4,000, 3 moles of maleic anhydride and 9.7% by weight of toluenesulfonic acid are added and reacted at a temperature of 120°C for 420 minutes.

[0025] In some embodiments, the weight percentage of the liquid rubber resin is from 1 wt % to 10 wt %, such as 2 wt %, 5 wt %, or 8 wt %, based on the total weight of the resin composition. In some embodiments, the liquid rubber resin comprises LDM-03-07, LDM-02, 1,2-SBS, or a combination thereof.

[0026] In some embodiments, the weight percentage of the filler is 20% to 50% by weight, such as 30%, 35%, or 40% by weight, based on the total weight of the resin composition. In some embodiments, the filler is spherical and the particle size (D50) of the filler is 0.3 μm to 3 μm. In some embodiments, the filler has a maximum particle size (D99) of 10 μm or less. In some embodiments, the filler includes a surface modification such as acrylic or vinyl. In some embodiments, the filler is SiO2, a filler provided by Third Age Technology.

[0027] In some embodiments, the resin composition further comprises a coupling agent. In some embodiments, the weight percentage of the coupling agent is 0.1% to 3% by weight, such as 0.5%, 1%, or 1.5% by weight, based on the total weight of the resin composition. The addition of the coupling agent can increase the compatibility and crosslinking degree of the resin composition with the glass fiber cloth or powder. In some embodiments, the content of the coupling agent in the resin composition is 0.1 parts (phr) to 3 phr of coupling agent per 100 parts by weight of resin. In some embodiments, the content of the coupling agent in the resin composition is about 1 phr. In some embodiments, the coupling agent is a siloxane coupling agent. In some embodiments, the coupling agent is a vinyl silane or an acrylic silane. In some embodiments, the coupling agent is a coupling agent provided by DOW under the trade name Z-6030.

[0028] In some embodiments, the resin composition further comprises a flame retardant. In some embodiments, the weight percentage of the flame retardant is 10% to 20% by weight, such as 12%, 15%, or 18% by weight, based on the total weight of the resin composition. In some embodiments, the flame retardant is a phosphorus-based flame retardant. In some embodiments, the flame retardant is a flame retardant available from Daihachi Chemical Industry Co., Ltd. under the trade name PX200.

[0029] In some embodiments, the resin composition further comprises a catalyst. In some embodiments, the weight percentage of the catalyst is 0.1 wt % to 2 wt %, such as 0.5 wt %, 1 wt %, or 1.5 wt %, based on the total weight of the resin composition. In some embodiments, the content of the catalyst in the resin composition is preferably 0.5 phr to 1.2 phr. In some embodiments, the catalyst is a catalyst provided by ARKEMA under the trade name DCP.

[0030] The resin composition of the present invention is suitable for forming a substrate for an electronic component. In some embodiments, the substrate is a copper foil substrate. In some embodiments, the substrate has the following specifications: a glass transition temperature (Tg) higher than 250°C (e.g., about 250°C to 260°C) and a dielectric loss tangent (Df) of about 0.02 or less. In some embodiments, the dielectric constant (Dk) of the substrate is about 3.2 or less (e.g., about 3.0 to 3.15). In some embodiments, the peel strength of the substrate is about 4.5 lb / in (e.g., about 4.5 lb / in to 5.2 lb / in). In some embodiments, the heat resistance of the substrate passes the test.

[0031] The implementation and effects of the present invention will be described in detail below using copper foil substrates made of resin compositions of the present embodiment and comparative examples, although the present invention is not limited to the following embodiments and comparative examples.

[0032] Based on the composition ratio in Table 1 below, the resin composition is mixed with MEK to form a varnish of a thermosetting resin composition. The resulting varnish is impregnated into a Nanya glass fiber cloth (NANYA Plastics Industry Co., Ltd., cloth model 1078LD) at room temperature, and then dried at about 130°C (the temperature of the impregnation machine) for several minutes to obtain a prepreg having a resin content of 60% by weight. After that, four pieces of prepreg are laminated between two pieces of copper foil with a thickness of about 35 μm, and the four pieces are dried at 25 kg / cm. 2 The mixture is kept at a temperature of 85°C under pressure for 20 minutes, heated to 210°C at a heating rate of 3°C per minute, kept at a constant temperature for 120 minutes, and then slowly cooled to 130°C to prepare a 0.5 mm thick copper foil substrate.

[0033] In Examples 1 to 6, the "DCPD-BMI" used is a bismaleimide resin (DCPD-MI) having a structure represented by formula (2).

[0034] In Examples 2 to 4, "KI-50P" and "KI-70" used are bismaleimide resins of the KI-50P and KI-70 series, respectively, sold by KI Chemical Co., Ltd.

[0035] In Examples 1, 2, 4, and 5, and Comparative Example 5, "LDM-03-07" and "LDM-02" used are liquid rubber resins of the LDM-03-07 and LDM-02 series, respectively, sold by Dainippon Ink and Chemicals, Inc.

[0036] In Examples 3 and 6, Comparative Examples 1, 3, and 5, the "1,2-SBS" used is a liquid rubber resin in the 1,2-SBS series of products sold by Nippon Soda.

[0037] In Comparative Examples 1 to 6, "RI 257" and "RI 184" used are liquid rubber resins of the RI 257 and RI 184 series, respectively, sold by CRAY VALLEY.

[0038] In Examples 1 to 6 and Comparative Examples 1 to 6, the "PX200" used is a flame retardant in the PX200 series, a trade name of which is sold by Daihachi Chemical Industry Co., Ltd.

[0039] In Examples 1 to 6 and Comparative Examples 1 to 6, the "DCP" used is a catalyst sold by ARKEMA under the trade name DCP series.

[0040] In Examples 1 to 6 and Comparative Examples 1 to 6, the "Z-6030" used is a siloxane coupling agent of the Z-6030 series, a trade name sold by DOW.

[0041] In Examples 1 to 6 and Comparative Examples 1 to 6, the SiO2 used is a SiO2 filler sold by Third Age Technology.

[0042] The copper foil substrate was evaluated for properties such as glass transition temperature, dielectric constant, dielectric loss tangent, peel strength, and heat resistance by the methods described below. The evaluation results are shown in Table 1.

[0043] Glass transition temperature (Tg)

[0044] The glass transition temperature (Tg) of the resin composition in the copper foil substrate was measured using a dynamic mechanical analyzer (DMA). A high Tg indicates that the resin composition has a good ability to resist phase change, i.e., good heat resistance.

[0045] Dielectric constant (Dk)

[0046] The dielectric constant at a frequency of about 10 GHz was measured using a dielectric analyzer (Model E4991A, manufactured by Agilent Technologies, Inc.) A small dielectric constant indicates that the resin composition in the copper foil substrate has good dielectric properties.

[0047] Dissipation factor (Df)

[0048] The dielectric loss tangent at a frequency of about 10 GHz was measured using a dielectric analyzer (Model E4991A, manufactured by Agilent Technologies, Inc.) A small dielectric loss tangent indicates that the resin composition in the copper foil substrate has good dielectric properties.

[0049] Peel strength

[0050] The peel strength between the prepreg and the copper foil was tested according to the IPC-TM-650-2.4.8 test method.

[0051] heat resistance

[0052] The copper foil substrate samples were heated in a pressure cooker at 120°C and 2 atm pressure for 120 minutes, then immersed in a soldering furnace at 288°C, and the time it took for the board to burst was recorded. Boards that took longer than 10 minutes to burst were marked as OK, and those that took less than 10 minutes were marked as NG.

[0053] [Table 1] JPEG2025031441000005.jpg86166

[0054] <Evaluation Results>

[0055] From Examples 1 to 6 in Table 1, it can be seen that the copper foil substrates made from the resin compositions having the component ratios of the present invention have Tg values ​​higher than 250° C., dielectric loss tangent Df values ​​less than 0.002, and dielectric constants Dk values ​​less than 3.2. Furthermore, the copper foil substrates of Examples 1 to 6 also exhibit good peel strength (≧4.5 lb / in) and good heat resistance.

[0056] From Comparative Examples 1 to 6 in Table 1, it can be seen that when the weight percentage of the bismaleimide resin is less than 30% by weight or more than 60% by weight, the measured Tg values ​​are all lower than 250° C. In addition, from Comparative Examples 1, 3, and 5, it can be seen that when the weight percentage of the liquid rubber resin is higher than 10% by weight, the measured Tg is lower than 165° C., and the performance of peel strength and heat resistance is poor. [Industrial Applicability]

[0057] In summary, the resin composition of the present invention uses bismaleimide resin as the main structure together with liquid rubber resin, and besides providing high glass transition temperature and low dielectric loss tangent, it also provides a non-polar skeleton structure. Therefore, it is not easily polarized in an electric field, thereby greatly reducing the dielectric constant. In addition, the resin composition of the present invention can be directly or indirectly applied to copper foil substrates, and can be further processed into other household, industrial, or suitable electronic components or electronic products (e.g., circuit boards or copper foil substrates). In addition, when applied to copper foil substrates, the resin composition of the present invention is beneficial to lower the dielectric loss tangent, improve the peel strength, and / or improve the heat resistance.

Claims

1. Based on the total weight of the resin composition, 30% to 60% by weight of a bismaleimide resin; 1% by weight to 10% by weight of a liquid rubber resin; 20% to 50% by weight of a filler; Including, Resin composition.

2. The bismaleimide resin comprises DCPD-BMI, KI-50P, KI-70, or a combination thereof; The resin composition according to claim 1.

3. The liquid rubber resin comprises LDM-03-07, LDM-02, 1,2-SBS, or a combination thereof; The resin composition according to claim 1.

4. further comprising 0.1% to 3% by weight of a coupling agent and 0.1% to 2% by weight of a catalyst; The resin composition according to claim 1.

5. Further comprising 10% to 20% by weight of a flame retardant; The resin composition according to claim 4.

6. A substrate formed from the resin composition according to claim 1. Electronic components.

7. The glass transition temperature of the substrate is 250° C. or higher. The electronic component according to claim 6.

8. the substrate has a dielectric loss tangent of 0.002 or less at a frequency of about 10 GHz; The electronic component according to claim 6.

9. The substrate has a dielectric constant of 3.2 or less at a frequency of about 10 GHz. The electronic component according to claim 6.

10. The substrate is a copper foil substrate; The electronic component according to claim 6.

Citation Information

Patent Citations

  • Curable resin composition

    JP1992055457A

  • Prepreg, multilayer group wiring board using it, and electronic component

    JP2008266408A

  • Resin varnish, prepreg, metal-clad laminate, printed wiring board and semiconductor device

    JP2012116941A

  • Resin composition, prepreg, laminate, multilayer printed board and method for manufacturing multilayer printed board

    JP2017071689A

  • Resin composition, prepreg containing the same, laminate containing the same, and resin-attached metal foil containing the same

    JP2021515823A